PERANCANGAN BUKU BERGAMBAR UNTUK ANAK BERJUDUL “SENYUM SEHAT GIGI TERAWAT” - Annisa Kurniawati S1 (Saraswati)
Caring for your teeth is to be done by each person. Guide and teach how to care for teeth habits in children from an early age the child accustomed to maintain health and hygiene his teeth into adulthood. Caring for your teeth is not difficult from the most basic brush your teeth twice a day is enough to protect teeth from bacteria on the teeth. check every six months to the dentist should also be made for dental hygiene, dental caries or eliminate food debris left on the teeth and no toothbrush affordable when brushing your teeth. How to care for your teeth properly brush your teeth in the direction and the correct procedures to prevent dental caries in children. The habit of eating sweet foods such as candy, chocolate, ice cream and others can cause dental caries if not immediately clean your teeth after eating them. Some things bad habits can cause dental caries as drinking a bottle pacifier when going to sleep, bite the fingers etc.. Some things can only make a bad habit of negative impact for children and adults anka, therefore that from now on maintaining and caring for hygiene should not be overlooked. Keywords: care, hygiene, dental caries